Efficacy of different herbicides on weed dynamics and productivity of kharif maize (Zea mays) and their residual effect on succeeding wheat crop (Triticum aestivum) - SINGH, AJAY; CHAND, MEHAR; PUNIA, S S; SINGH, NARENDER; RANA, SANDEEP S (The Indian Journal of Agricultural Sciences, 2020)
Weeds are the major biotic constraints in maize crop due to its wider row spacing limiting its productivity. So, a field experiment was conducted during kharif and rabi seasons of 2015 and 2016, at RRS, Karnal, Haryana to study the effect of different weed control methods on weed flora, growth and yield of kharif planted maize, the residual effect of different herbicides applied in maize on succeeding wheat crop. Treatments included two pre-emergence (PRE) herbicides namely atrazine 750 or 1000 g/ha and alachlor 2000 g/ha along with three post-emergence herbicides (POST) atrazine 500 g/ha, 2,4-D 500 g/ha and tembotrione 120 or 140 g/ha +S (surfactant) at 35 days after sowing (DAS) were used. Hand weeding twice at 20 and 35 DAS, weedy check and weed free treatments were also included. Major weed species infesting the experimental field were Cyperus rotundus, Brachiaria reptans, Dactyloctenium aegyptium, Amaranthus viridis, Digera arvensis, Phyllanthus niruri and Portulaca oleracea. Among herbicide treatments at 50 DAS, alachlor 2000 g/ha as PRE fb tembotrione 120 g/ha provided the highest weed control efficiency (95.1 %). Maximum grain yield (6505 and 6903 kg/ha) and yield attributes of maize were obtained in weed free treatment which was statistically at par with alachlor 2000 g/ha fb tembotrione 120 g/ha +S at 35 DAS (T13) (6380 and 6816 kg/ha). No visual phyto-toxicity of any applied herbicide was observed on maize crop. All herbicide treatments employed in kharif maize, irrespective of their dose and application time did not show any residual carryover effect on succeeding wheat crop.